Subversion version control : using the Subversion version control system in development projects - Nagel, William A. (Bruce Perens' Open Source series., 2005)
In any software development project, many developers contribute changes over a period of time. Using a version control system to track and manage these changes is vital to the continued success of the project. This book introduces you to Subversion, a free, open-source version control system, which is both more powerful and much less complex than its predecessor CVS. In this practical, hands-on guide, you will learn how to use Subversion and how to effectively merge a version control system within your development process. As a seasoned Subversion user, William Nagel draws on lessons learned through trial and error, providing useful tips for accomplishing tasks that arise in day-to-day software development. Nagel clearly explains how to expand on the built-in abilities of Subversion, making the system work better for you. He organizes Subversion commands by activity to allow for quick task reference. Using example scripts and configurations, he also includes development approaches that you can customize to fit your own environment. Inside, you will find A guide to installing Subversion on Linux, Windows, and Mac OS X. A tutorial walkthrough of Subversion, from creating your first repository to basic branching and merging. A detailed look at the most important Subversion client commands, as well as properties, user configuration, and integration with a variety of external tools. A guide to repository administration and organization, including repository security and migration from another version control system. An in-depth look at automation in Subversion, including using hook scripts, metadata, and the Subversion API, plus example scripts. Case studies that examine both archetypal and real-world projects and their use of Subversion. A Subversion command reference for fast access to essential technical information. Details on Subversion's many advanced features, such as its Apache-integrated WebDAV server and database file storage system. Whether you are an administrator, project manager, or software developer, Subversion Version Control will show you how to realize the full potential of Subversion.